Ophthalmic manifestations and management of common and rare autoimmune syndromes. Issue 5 (October 2020) - Seol, Young; Lee, Roxanne; Bielory, Brett P.
Abstract : Purpose of review: This article reviews the ocular findings in patients with a myriad of autoimmune syndromes. This review will provide guidance and heighten awareness for the allergist or eye care provider to pay heed to the manifestations and treatments of autoimmune syndromes. Recent findings: Autoimmune syndromes can present with varied manifestations on the ocular surface known to potentially cause significant visual morbidity. In particular, sterile corneal ulcers are the most devastating and common finding in uncontrolled autoimmune disease. Ophthalmic manifestations of autoimmune syndromes have been reported individually; however, herein we present a comprehensive review of typical and atypical syndromes that may present with sterile corneal ulceration. Summary: Autoimmune inflammatory syndromes are known to be associated with ocular surface inflammatory processes ranging from bothersome dry eye syndromes to vision-threatening sterile corneal ulceration. It is important to pay heed to the clinical presentation of common and uncommon presentations of the syndromes in the eye. We propose best practice for management of ocular surface disease in these clinical entities.